TAX PLANNING AND FIRMS’ LIQUIDITY - .N, 1NWAOBIA Appolos; O, JAYEOBA, Olajumoke. (IJRDO - Journal of Business Management, 2016)
Tax expense is a significant cost to organizations as it affects their cash flow and workingcapital. As a result of this, organizations all over the world adopt tax planning strategies targetedat minimizing their tax liability without adversely affecting the overall financial liquidity of thefirm. Thus, this study empirically examined the effect of tax planning strategies on firms’liquidity. Various tax planning strategies were discussed but the strategies of Capital Intensity(CAPINT), Thin Capitalization (TINCAP), Lease Option (LOPT) and Industry sector incentives(IND) were selected as the independent variable. The Criterion variable used was firms’ liquiditymeasured in this study by the Current Ratio (CR) while firm size (SIZE) was adopted as thecontrol variable. Data obtained from 154 firm- year observations were described and regressionanalysis was used to test the hypothesis developed. The results reveal that tax planning strategiesof Capital Intensity (CAPINT), Thin Capitalization (TINCAP), and Lease Option (LOPT) exertnegative effects on firms’ liquidity while tax planning strategies of Industry (IND) and firm size(SIZE) have positive effects on firms’ liquidity. This implies that tax planning as a balancing actrequires possession of specialist knowledge and skills to effectively craft in order for it topositively impact firms’ liquidity as well as enhance firm value. Thus, it was recommended thatappropriate measures and skill should be applied in determining appropriate mix of strategies toadopt for tax planning purpose as some strategies if not properly designed and applied mayreduce tax liability at the expense of firm’s liquidity.